New Halophilic Community Degrades Plastics: A Metagenomic Study - Nikolay Krumov; Nikolina Atanasova; Ivanka Boyadzhieva; Tsvetelina Paunova-Krasteva; Kaloyan Berberov; Kaloyan Petrov; Penka Petrova (Fermentation)
Biodegradation is an advanced method for reducing plastic waste in the environment, involving the participation of microbial communities with plastic-degrading properties. Our study presents a novel halophilic community isolated from the plastic-contaminated region in Burgas Lake, Bulgaria. In a medium containing 15% sodium chloride, the community can degrade a significant amount of polycaprolactone (PCL) as a sole carbon source, as well as the plastics polystyrene (PS) and polypropylene (PP), albeit to a lesser extent. The community showed high hydrophobicity and the ability to form a biofilm on PCL beads, as well as high esterase activity and significant biodegradation capacity, as demonstrated by measuring the weight of the PCL material after cultivation for 4 and 8 weeks. Moreover, a scanning electron microscopy (SEM) analysis revealed visible cracks, craters, and holes in the surface of the polymer particles. The metagenomic study revealed that Halomonas profundus dominated the community with a proportion of 95.13%, followed by Alloalcanivorax venustensis (2.73%), Chromohalobacter marismortui (0.72%), and Halomonas caseinilytica (0.78%). However, most of the species in the community were not previously known as PCL-degrading. Thus, studying the diversity of the halophile community can significantly improve our fundamental understanding and clarify their potential applications for environmental and water–plastic remediation.